Creating New Futures: Settling Children and Youth from Refugee Backgrounds, edited by Mary Crock - Hess, Julia Meredith (Refuge: Canada's Journal on Refugees, 2016)
Creating New Futures: Settling Children and Youth from Refugee Backgrounds Edited by Mary Crock Sydney: Federation, 2015, pp. 313